2009
DOI: 10.1080/08927010903419630
|View full text |Cite
|
Sign up to set email alerts
|

Biofouling control using microparticles carrying a biocide

Abstract: This study presents a new technological approach to minimize the use of antimicrobial (AMB) agents and their deleterious effects, based on the principle of drug-delivery systems whereby the AMB chemicals are transported on microparticles. The efficacy of microparticles carrying the quaternary ammonium compound (QAC), benzyldimethyldodecyl ammonium chloride (BDMDAC), was assessed against Pseudomonas fluorescens in both the planktonic and the biofilm state. The microparticles were prepared using a layer-by-layer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 39 publications
1
21
0
Order By: Relevance
“…The biofilm habitat represents a primary mode of growth for most microorganisms on earth (Flemming 2002;Ferreira et al 2009). It has been shown that biofilms are more resistant to toxic chemicals such as heavy metals and antimicrobial agents than planktonic cells (Choi et al 2010).…”
Section: Effect Of Biogenic Silver (Bio-ag 0-6 ) On Established Biofilmsmentioning
confidence: 99%
“…The biofilm habitat represents a primary mode of growth for most microorganisms on earth (Flemming 2002;Ferreira et al 2009). It has been shown that biofilms are more resistant to toxic chemicals such as heavy metals and antimicrobial agents than planktonic cells (Choi et al 2010).…”
Section: Effect Of Biogenic Silver (Bio-ag 0-6 ) On Established Biofilmsmentioning
confidence: 99%
“…Biofilms were grown on 24 ASI 316 stainless steel (SS) slides (2.5 cm 6 2.5 cm and 1 mm thick) that were hung within the chemostat system ( Figure 1). The chemostat system was operated at 27 + 28C, with aeration (air flow rate -0.350 min 71 ) and stirring (VWR, VMS-C7 Advanced; 120 rpm; stirrer length -2.5 cm), according to previous studies (Pereira and Vieira, 2001;Simo˜es et al 2003a;Ferreira et al 2010). The biofilms were allowed to grow for 6 days, which was the time needed to reach the steady state in terms of cell density, metabolic activity and mass (Pereira and Vieira 2001).…”
Section: Biofilm Reactormentioning
confidence: 99%
“…One of the earliest observations related to the different characteristics observed in planktonic and biofilm cells was the increased resistance of cells in biofilms to antimicrobial agents and adverse environmental conditions (Drenkard and Ausubel 2002;McBain et al 2002;Simo˜es et al 2008a;Ferreira et al 2010). However, it is not known why and how bacteria, growing within a biofilm, develop increased resistance to antimicrobial agents.…”
Section: Introductionmentioning
confidence: 99%